An arsenal of tools based on Kendrick mass defects to process congested electrospray ionization high‐resolution mass spectra of polymers with multiple charging. (8th February 2020) - Ishitsuka, Kei; Kakiuchi, Toshifumi; Sato, Hiroaki; Fouquet, Thierry N. J.
Abstract : Rationale: Electrospray ionization (ESI) favors the multiple charging of high molecular weight polymer samples and allows their high‐resolution mass analysis in the low‐mass range. It also induces the detection of numerous ion series at different charge states with different adducts complicating the interpretation of the mass spectrum which should be facilitated by an appropriate data processing. Methods: An arsenal of tools based on the Kendrick mass defect (KMD) is proposed to process congested ESI high‐resolution mass spectra of poly(propylene oxide) (PPO) samples. The combination of regular, charge‐dependent, and resolution‐enhanced KMD plots in addition to a "remainders" plot and a new three‐dimensional plot offers unrivaled capabilities of filtering for any minor series among thousands of points. The sequential data processing is conducted using Kendo, a spreadsheet developed in‐house for an advanced KMD analysis. Results: The charge‐state distribution is easily evaluated by counting the parallel lines in a regular KMD plot. A charge‐dependent resolution‐enhanced KMD plot instantly reveals the variation of adducted ions at a given charge state, helping the user to choose the best analytical conditions. Ion series at different charge states from PPO oligomers carrying different end‐groups are also efficiently extracted using several combinations of KMD and remainders plots and assigned using a new simulator tool. Conclusions: The innovative combination of existing and new KMD‐related plots, selection tools, and simulator all combined in a single spreadsheet dramatically facilitates the processing and interpretation of complex ESI mass spectral data. The presented tools may be extended to any other class of homo‐, co‐ and terpolymers.